Influence of CFD Modelling Parameters on Air Injection Behaviour in Ship Air Lubrication Systems - Gyeongseo Min; Haechan Yun; Younguk Do; Kangmin Kim; Keounghyun Jung; Saishuai Dai; Mehmet Atlar; Daejeong Kim; Seungnam Kim; Sanghyun Kim; Soonseok Song (Journal of Marine Science and Engineering, 2026)
In response to the International Maritime Organization’s strengthened regulations on carbon emissions, the introduction of novel eco-friendly technologies for ship operators has become necessary. In this context, various energy saving devices such as wind-assisted propulsion systems (e.g., wing/rotor sails), propeller-rudder efficiency enhancers (e.g., pre-swirl stators or ducted propellers), and the gate rudder system have been proposed. Among various energy-saving technologies, the air lubrication system has been widely investigated as an effective means of reducing hull frictional resistance through air injection beneath the hull. The performance of air lubrication systems can be evaluated through experimental testing or computational fluid dynamics (CFD) simulations. However, accurately simulating air lubrication systems in CFD remains challenging. Therefore, this study aims to quantitatively evaluate the influence of numerical parameters on the CFD implementation of air lubrication systems. To evaluate these influences, CFD simulations employing the unsteady Reynolds-averaged Navier–Stokes (URANS) method were conducted to investigate air layer formation and sweep angle on a flat plate. The numerical predictions were systematically compared with experimental results by varying key numerical parameters. These quantitative estimations of the effects of numerical variables are expected to serve as a useful benchmark for CFD simulations of air lubrication systems.